Tata Kelola Laut dan Pesisir Berbasis Kearifan Lokal Desa Lewomuda Kabupaten Flores Timur - Kristianus Simon Hale Molan; Hendrikus Likusina Kaha; Frans Nyong; Frans Bapa Tokan; Yosef Dionisius Lamawuran (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Increased exploration of coastal and marine areas can damage the environment and threaten ecosystem sustainability. Renewal of governance based on local values is needed. The article seeks to introduce local values in the Letu Ai and Lara Lowa rituals while offering a local value-based governance model. This research is a descriptive qualitative research. Ritual analysis unravels local values: ecosystem harmonization; religiosity, social integration and the existence of customary institutions. Governance reform is directed at improving conservation points and systems; increasing ethical awareness in the form of environmental respect attitudes and behaviors; local government intervention to protect the existence of customary institutions, involving the active role of young people in maintaining ancestral heritage.